7(u-1)=4u+8

Simple and best practice solution for 7(u-1)=4u+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(u-1)=4u+8 equation:


Simplifying
7(u + -1) = 4u + 8

Reorder the terms:
7(-1 + u) = 4u + 8
(-1 * 7 + u * 7) = 4u + 8
(-7 + 7u) = 4u + 8

Reorder the terms:
-7 + 7u = 8 + 4u

Solving
-7 + 7u = 8 + 4u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-4u' to each side of the equation.
-7 + 7u + -4u = 8 + 4u + -4u

Combine like terms: 7u + -4u = 3u
-7 + 3u = 8 + 4u + -4u

Combine like terms: 4u + -4u = 0
-7 + 3u = 8 + 0
-7 + 3u = 8

Add '7' to each side of the equation.
-7 + 7 + 3u = 8 + 7

Combine like terms: -7 + 7 = 0
0 + 3u = 8 + 7
3u = 8 + 7

Combine like terms: 8 + 7 = 15
3u = 15

Divide each side by '3'.
u = 5

Simplifying
u = 5

See similar equations:

| 48-8*2= | | 9(3x-2x)=2(10-8x) | | 7(y+9)=92 | | s-y=w | | 50-6*6= | | -5-6(3b+1)=39-8b | | -5x-6(x-5)=-x+30 | | 4(w+3)=8w | | 3x-11=x^2-9 | | D^2+8*d+9=0 | | 15-3*4= | | 4x^2-5=-5x+3 | | 3x+24y=9 | | -(8-4r)=-5+4r | | 24x^2+2xy-y^2=0 | | 23+5x=-2(x+6) | | 7(1+8v)+2v=7-6v | | 6(1-2x)-5=-83 | | 24x^2+2xr-r^2=0 | | 2x^3+x^2-19x+36=y | | -[2]=x-9 | | -2(v+3)=-18 | | x^2+1.68=2.6x | | 5(-4+m)=-45 | | 2x^3+x^2-19x+36=x | | -5r-3=-33 | | 6(4x+7)=105 | | 5(n+5)=34+8n | | f(x)=2x^3+x^2-19x+36 | | 3(x+2.5)=-7.5 | | x+6-2x-4=0 | | 9+3(2x-6)=14 |

Equations solver categories